Conjoint board of general surgery panels, site visit to Hospital Al-Sultan Abdullah, UiTM 2025 - Abdul Rashid, Nor Faezan; Yusoff, Ahmad Ramzi; Che Ani, Mohd Firdaus; Osman, Nora Julianna; A. Karim, Zeti Rahayu; Krishnasamy, Theevashini; Ahmad Nazlan, Mohd Fadhil; Jawad Obaid, Kadhim; Abd Hamid, Muhammad Syamil (Faculty of Medicine, 2025)
On the 15th of January 2025, the Department of Surgery was delighted to receive a visit from the Conjoint Board of General Surgery to Hospital Al-Sultan Abdullah (HASA), UiTM. This was their second visit to HASA as part of a follow-up in preparation for the start of our Master of Surgery program. The panel consisted of representatives from four main universities that offer the program, as well as from the Ministry of Health. They were Associate Professor Dr. Maya Mazuwin Yahya from Universiti Sains Malaysia, who is also the Chairman of the Conjoint Board; Associate Professor